Survey of technologies of self-organizing networks (SON) - Sharama, Apurva; Jaswinder Singh, Dr. (International Journal of Engineering and Technology, 2018)
Due to increase in existing web availability, self organized systems are expected to give a quick, adaptable and cost-effective solution for satisfy the gap between limit and request/demand to adapt to the quick development in remote activity or wireless traffic. The main purpose of introducing SON algorithm is to simplify the network operations via automating repeated tasks in network operations. Hence, in SON empowered system operations, methods that hold the human administrator in manual system operations are substituted via programmed SON functions. Self organized systems or intelligent frameworks are required for remote portable systems to deal with broad number of clients in the meantime and to support the human administrator in manual system operations; that are substituted via automatic SON functions since the human administrators don't have to gather and examine the system information. Self organized networks are needed for the controlling the big challenge of mobile traffic growth and to reduce the cost efficiency. Efficient methods are required for automatic channel selection, power adjustment, and frequency assignment for autonomous interference coordination and coverage optimization.Â